2021
DOI: 10.1177/1524839921996083
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Community Art and Its Role in Promoting Health, Social Cohesion, and Community Resilience in the Aftermath of the 2015 Nepal Earthquake

Abstract: A magnitude 7.8 earthquake struck Nepal in 2015, followed by hundreds of aftershocks that led to physical destruction, loss, and negative mental health outcomes. Yet, in the days, months, and years following the disaster, numerous forms of community art rose from the rubble, such as urban murals, spoken word poetry, public dance performances, and sacred art. This study explored the relationship between community art and health, social cohesion, and community resilience in postearthquake Nepal. We utilized phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…When combining arts and science as a strategy for knowledge translation it is important to collaborate with stakeholder groups to identify the need for an arts-based strategy, as well as what art form is most appropriate to convey the messaging ( Archibald et al, 2018 ). Community art, art freely available in community spaces, can promote health, social cohesion and community resilience post disasters ( Baumann et al, 2021 ). For instance, Baumann and Burke (2021) created a virtual art gallery for community members to submit artwork representing connection during the COVID-19 pandemic and found that the act of creating art itself had mental health and social benefits.…”
Section: Discussionmentioning
confidence: 99%
“…When combining arts and science as a strategy for knowledge translation it is important to collaborate with stakeholder groups to identify the need for an arts-based strategy, as well as what art form is most appropriate to convey the messaging ( Archibald et al, 2018 ). Community art, art freely available in community spaces, can promote health, social cohesion and community resilience post disasters ( Baumann et al, 2021 ). For instance, Baumann and Burke (2021) created a virtual art gallery for community members to submit artwork representing connection during the COVID-19 pandemic and found that the act of creating art itself had mental health and social benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Observing or creating community art or mural paintings can offer relief and therefore is a mechanism for coping. It also enhances community cohesion and can be utilised to create emotional safety spaces (27).…”
Section: Discussionmentioning
confidence: 99%
“…murals, film, dance) could be delivered in high‐density traffic spots (e.g. GP waiting rooms, bus stops, aged care homes, libraries) 21 frequented by cultural groups. A recent initiative addressing widespread awareness in multicultural communities ( Moving Pictures ) shows excellent promise.…”
Section: Public Health Initiativesmentioning
confidence: 99%